2013
DOI: 10.1098/rstb.2013.0028
|View full text |Cite
|
Sign up to set email alerts
|

The structure and evolution ofcis-regulatory regions: theshavenbabystory

Abstract: In this paper, we provide a historical account of the contribution of a single line of research to our current understanding of the structure of cis-regulatory regions and the genetic basis for morphological evolution. We revisit the experiments that shed light on the evolution of larval cuticular patterns within the genus Drosophila and the evolution and structure of the shavenbaby gene. We describe the experiments that led to the discovery that multiple genetic changes in the cis-regulatory region of shavenb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 48 publications
1
60
0
Order By: Relevance
“…It should be noted however that even if eQTLs are shared, we are not sure whether the causative mutations are shared (Conte, Arnegard, Schluter, & Peichel, ; Rosenblum, Parent, & Brandt, ). As in the case of Drosophila (Stern & Frankel, ), multiple mutations may accumulate at a QTL, indicating that a single QTL does not mean a single mutation.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted however that even if eQTLs are shared, we are not sure whether the causative mutations are shared (Conte, Arnegard, Schluter, & Peichel, ; Rosenblum, Parent, & Brandt, ). As in the case of Drosophila (Stern & Frankel, ), multiple mutations may accumulate at a QTL, indicating that a single QTL does not mean a single mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Elegant studies have revealed that regulation of Svb controls dorsal and ventral cuticle patterning in drosophilids (reviewed by Delon and Payre, 2004;Stern and Frankel, 2013) through its activation of numerous effector molecules (Chanut-Delalande et al, 2012). Yet whether and how Svb activity might control the row-specific shapes of ventral denticles has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Classical genetics approaches have provided evidence of redundant, additive, and synergistic enhancer relationships at a handful of loci (Banerji et al, 1983; Banerji et al, 1981; Bender et al, 2012; Blasquez et al, 1992; de Villiers and Schaffner, 1981; Fujioka et al, 1999; Fulton and van Ness, 1994; Guo et al, 2012; Hong et al, 2008; Kehayova et al, 2011; Lam et al, 2015; Montavon et al, 2011; Perry et al, 2010; Small et al, 1992; Stern and Frankel, 2013). For example, two enhancers regulating Pomc are both necessary in the mouse embryo, indicating a synergistic relationship, while the enhancers contribute additively to Pomc expression in adult mice (Lam et al, 2015).…”
Section: Introductionmentioning
confidence: 99%